2018
DOI: 10.3390/ijerph15112407
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Opportunities and Challenges of the Digital World for Early Childhood Services with Vulnerable Children

Abstract: Potentially addictive behaviours supported by the internet and mobile phones raise concerns in education services for early childhood. Although there is evidence that screen media can distract the attention of young children, there was a massive uptake of digital devices by early childhood centres (ECCs). We investigated practices of families (n = 85) and of six ECCs serving vulnerable children in New Zealand, many of whom are emergent bilinguals. Descriptions of the limited and exemplary choice of screen medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…The ecosystems documented in this study showed an increasing presence of Māori, the indigenous language of New Zealand, and of the additional home languages of the young children who inhabited them (Harris, Davis et al , ). There was indirect evidence from teacher interviews that a few multilingual families thought it was best for their children to focus on English, until advised otherwise.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The ecosystems documented in this study showed an increasing presence of Māori, the indigenous language of New Zealand, and of the additional home languages of the young children who inhabited them (Harris, Davis et al , ). There was indirect evidence from teacher interviews that a few multilingual families thought it was best for their children to focus on English, until advised otherwise.…”
Section: Discussionmentioning
confidence: 79%
“…Families within the wider project’s survey reported that 6.8% of children did not engage with any digital media while 32% engaged with digital media for more than 5 hours per week (Harris, Davis et al , ); the teachers were concerned about excessive screen time. The bilingual parent interviewed described her management of the digital world (DW) in her home ecosystem showing that as a parent she was acting as the keystone species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ponte et al (2017) estabeleceram uma relação com o nível socioeconómico das famílias, e viram que o consumo televisivo das crianças é maior nos lares com baixos rendimentos, enquanto aquelas que pertencem a um estrato económico superior possuem mais acesso à internet nos vários dispositivos existentes no espaço doméstico. A este propósito, Harris et al (2018) verificaram que as crianças economicamente desprovidas, sobretudo quando pertencem a minorias étnicas, tendem a apresentar um défice de "literacia digital", por falta de acesso a dispositivos e a conteúdos conectados à internet.…”
Section: Especificidades Sociodemográficas Da Exposição E Mediação Dounclassified